Epidemiological and clinical features of SARS‐CoV‐2 infection in children during the outbreak of Omicron variant in Shanghai, March 7–31, 2022. Issue 6 (31st August 2022) - Wang, Xiangshi; Chang, Hailing; Tian, He; Zhu, Yanfeng; Li, Jingjing; Wei, Zhongqiu; Wang, Yixue; Xia, Aimei; Ge, Yanling; Liu, Gongbao; Cai, Jiehao; Zhu, Qirong; et al.
Abstract: Objectives: This study aimed to understand the epidemiological and clinical characteristics of pediatric SARS‐CoV‐2 infection during the early stage of Omicron variant outbreak in Shanghai. Methods: This study included local COVID‐19 cases <18 years in Shanghai referred to the exclusively designated hospital from March 7 to March 31, 2022. Clinical data, epidemiological exposure, and COVID‐19 vaccination status were collected. Relative risks (RRs) were calculated to assess the effect of vaccination on symptomatic infection and febrile disease. Results: A total of 376 pediatric cases of COVID‐19 (median age: 6.0 ± 4.2 years) were referred to the designated hospital, including 257 (68.4%) symptomatic cases and 119 (31.6%) asymptomatic cases. Of the 307 (81.6%) children ≥3 years eligible for COVID‐19 vaccination, 110 (35.8%) received two doses of vaccines. The median interval between the completion of two‐dose vaccination and infection was 3.5 (interquartile range [IQR]: 3, 4.5) months. Compared with no vaccination, two‐dose COVID‐19 vaccination reduced the risks of symptomatic infection and febrile disease by 35% (RR 0.65, 95% confidence interval [CI]: 0.53–0.79) and 33% (RR 0.64, 95% CI: 0.51–0.81) among confirmed cases. Eighty‐four percent of symptomatic cases had fever (mean duration: 1.7 ± 1.0.8 days), 40.5% had cough, and 16.4% had transient leukopenia. Three hundred and seven (81.6%) had an epidemiological exposure in household (69.1%), school (21.8%), and residential area (8.8%). Conclusion: The surge of pediatric COVID‐19 cases and multiple transmission model reflect wide dissemination of Omicron variant in the community. Asymptomatic infection is common among Omicron‐infected children. COVID‐19 vaccination can offer some protection against symptomatic infection and febrile disease.